Polyphenol Stilbenes: Molecular Mechanisms of Defence against Oxidative Stress and Aging-Related Diseases - Reinisalo, Mika (Oxid Med Cell Longev, 2015)
Numerous studies have highlighted the key roles of oxidative stress and inflammation in aging-related diseases such as obesity, type 2 diabetes, age-related macular degeneration (AMD), and Alzheimer's disease (AD). In aging cells, the natural antioxidant capacity decreases and the overall efficiency of reparative systems against cell damage becomes impaired. There is convincing data that stilbene compounds, a diverse group of natural defence phenolics, abundant in grapes, berries, and conifer bark waste, may confer a protective effect against aging-related diseases. This review highlights recent data helping to clarify the molecular mechanisms involved in the stilbene-mediated protection against oxidative stress. The impact of stilbenes on the nuclear factor-erythroid-2-related factor-2 (Nrf2) mediated cellular defence against oxidative stress as well as the potential roles of SQSTM1/p62 protein in Nrf2/Keap1 signaling and autophagy will be summarized. The therapeutic potential of stilbene compounds against the most common aging-related diseases is discussed.